DAMPAK KAWASAN INDUSTRI DI DESA BUTUH TERHADAP PEREKONOMIAN DAN KEINGINAN BERWIRAUSAHA DI KECAMATAN MOJOSONGO, BOYOLALI - Istiqomah, Nurul; Prasetyani, Dwi (EP FEB UNS, 2014)
This background of this research is the establishment of several factories in Butuh Village, Mojosongo Sub-District, Boyolali Regency, which forms an industrial area. In the past, the residents of Butuh Village worked by cultivating land and breeding livestock because the soil in this area is barren and water sources are difficult to find. Because of the establishment of industrial area, the economic activity of this area increases significantly.This research uses descriptive-quantitative research method. Qualitative analysis is used to discover the increase of economic activity and the level of health and education of the surrounding community. Whereas quantitative analysis was conducted by using Paired Samples T test. This test is used to discover the presence of average difference between two paired (corresponding) sample groups. In this case, it is about community’s income and expenditure in the surroundings of industrial area. Whereas regression analysis, specifically Ordinary Least Square(OLS) Logit, is used to discover community’s entrepreneurship desire after the existence of industrial area.The impact of industrial area in Butuh Village, Mojosongo Sub-district can reduce unemployment rate. However,most people in Butuh Village prefer becoming entrepreneurs around the industrial area to factory workers. Additional income earned shifts the way of thinking of people around industrial area in the field of education and health. In addition, there were differences of income and expenditure between the times before and after the existence of industrial area in Butuh Village. The last, education, income and expenditure influence the entrepreneurial decision. Key words: Industrial Area, Income, Expenditure, Paired Samples T-test, Logit.